Didactique des langues-cultures, genre, intersectionnalité et empowerment féministe : un entretien avec Véronique Perry - Véronique Perry; Eléonore de Beaumont (Glad!)
For this second "Comparing Gender" column, I am interested in gender as it relates to interculturality and plurilingualism. I chose to interview Véronique Perry, one of the pioneers in research on the articulation of gender and the didactics of language & culture. Since the publication of her PhD thesis in 2011, Aspects du genre dans la didactique de l’anglais (Aspects of gender in English didactics), she has been developing a hybrid, feminist pedagogical approach to teaching English to science and technology students at the Université Toulouse Paul Sabatier. In this interview, I first discuss with her the danger of disciplinary compartmentalization, both for didactics of language & culture and for gender (Perry, 2003), and second, the evolution of what she calls "gender culture" (2011) in France and its influence on didactics. Finally, she talks about the empowering pedagogical measures she has put in place to circumvent learners’ resistance and enable them to emancipate themselves.